2020
DOI: 10.1016/j.tra.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A work-life conflict perspective on telework

Abstract: Highlights Life stages associate with telework behavior in a complex way. Irrespective of gender and marital status, parents are less likely to telework compared to those without children. Regarding individuals without children, single individuals are more likely to telework than married ones, and males are more likely to telework than females. For individuals with children, the partnered parents are more likely to telework than the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
119
0
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 81 publications
7
119
0
22
Order By: Relevance
“…Later, working at home was linked with the savings of gasoline [16]. In this vein, Zhang et al (2020) [17] affirm telework as the traffic demand management policies to mitigate congestion during rush hours and decrease work-related trips. Recent paper work discusses the potential advantages and disadvantages of eworking [18].…”
Section: -E-working: Conceptual Frameworkmentioning
confidence: 99%
“…Later, working at home was linked with the savings of gasoline [16]. In this vein, Zhang et al (2020) [17] affirm telework as the traffic demand management policies to mitigate congestion during rush hours and decrease work-related trips. Recent paper work discusses the potential advantages and disadvantages of eworking [18].…”
Section: -E-working: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies have suggested that the COVID-19 pandemic would cause great damages to China’s macro economy and sectoral output in the short run. While the shutdown of economic activities would significantly cut down the enterprises’ production, strict distancing would cause consumers to spend less ( Duan et al, 2020 ; Guan et al, 2020 ; Guerrieri et al, 2020 ; McKibbin and Fernando, 2020 ; Zhang et al, 2020 ). McKibbin and Fernando (2020) employed a dynamic computable general equilibrium (CGE) model and found that China’s GDP in 2020 would decline by 0.4–6.2% depending on the population mortality and duration of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…China (2020) , the total passenger volume of railway, road, waterway, and aviation transportations dropped by 50.9% in January and February of 2020, while the total freight volume fell by 19.7%. An increasing number of studies evaluated the relationship between the pandemic and transport sector, and regarded it as the major transmission route of infectious diseases ( Regondi et al, 2013 ; Cai et al, 2019 ; Gaskin et al, 2020 ; Jiao et al, 2020 ; Lau et al, 2020 ; Zhang et al, 2020 ; Przemysław et al, 2020 ). Zhang et al (2020) found that frequencies of flights and high-speed train services out of Wuhan had been significantly associated with the number of COVID-19 cases in the destination cities.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, teleworking contributed not only to people’s safety, but also to a drastic decrease in environmental pressure by reducing mobility [ 21 ]. However, the possible benefit on the family nucleus and the perception of the balance between home care and work activity was not so clear [ 22 ].…”
Section: Introductionmentioning
confidence: 99%